Pathways Linking Childhood Personality to Later Life Outcomes. (19th April 2019) - Hill, Patrick L.; Edmonds, Grant W.; Jackson, Joshua J.
Abstract: Dispositional characteristics are associated with important life outcomes across the lifespan, often predicting those outcomes decades in advance. Evidence demonstrates that personality characteristics measured during childhood and adolescence uniquely affect later life outcomes above and beyond adult personality. Currently, it is unclear why personality produces unique effects at different life stages, given the modest consistency of personality across the lifespan. In this article, we offer possible explanations for why these unique predictive effects may occur, charting pathways that link childhood personality to later outcomes that differ from how adult personality influences the same products. We conclude by suggesting directions for longitudinal investigations into when, why, and how assessments of childhood personality can help advance our understanding of lifespan development.